Proceedings of the 3rd International Conference on Information Systems Security and Privacy 2017
DOI: 10.5220/0006228504990505
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Protocols at the Rescue for Trustworthy Online Voting

Abstract: Abstract:While online services emerge in all areas of life, the voting procedure in many democracies remains paper-based as the security of current online voting technology is highly disputed. We address the issue of trustworthy online voting protocols and recall therefore their security concepts with its trust assumptions. Inspired by the Bitcoin protocol, the prospects of distributed online voting protocols are analysed. No trusted authority is assumed to ensure ballot secrecy. Further, the integrity of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The articles that we examined during the process can be categorized into five main groups (Table 4): (a) General: Many researchers published their conclusive research and pointed out that utilizing smart contracts on a blockchain platform will make a significant contribution to e-voting as it enables cost-efficiency and offers new possibilities to overcome limitations in the scalability of electronic voting systems. After reviewing both existing online voting systems and distributed systems, we have concluded that blockchain technology can be a solution that governments could adopt in order to obtain public voters' confidence and accountability [41,64,72]. From a practical point of view, in terms of development and exploitation, there are several distinct advantages and disadvantages of using blockchain-based smart contracts on electronic voting systems [79].…”
Section: Rq2: Can the Blockchain Concept Improve E-voting Systems?mentioning
confidence: 99%
“…The articles that we examined during the process can be categorized into five main groups (Table 4): (a) General: Many researchers published their conclusive research and pointed out that utilizing smart contracts on a blockchain platform will make a significant contribution to e-voting as it enables cost-efficiency and offers new possibilities to overcome limitations in the scalability of electronic voting systems. After reviewing both existing online voting systems and distributed systems, we have concluded that blockchain technology can be a solution that governments could adopt in order to obtain public voters' confidence and accountability [41,64,72]. From a practical point of view, in terms of development and exploitation, there are several distinct advantages and disadvantages of using blockchain-based smart contracts on electronic voting systems [79].…”
Section: Rq2: Can the Blockchain Concept Improve E-voting Systems?mentioning
confidence: 99%
“…In [Riemann and Grumbach, 2015], the authors introduce a taxonomy of further notions for distributed voting protocols.…”
Section: Related Workmentioning
confidence: 99%
“…An online voting system is an election system that store election data. It is important to have a safe voting platform to overcome problems during voters cast his/her vote [1]. The voting method that is usually used nowadays is a single-vote method, which is online single vote available and only one selected alternative.…”
Section: Introductionmentioning
confidence: 99%
“…MCDM is a very useful method that can make decision-making with more than one criterion [2]. The voters can make ranking in numerical analysis (1)(2)(3)(4)(5) based on different criteria. This method is less time-consuming to the voters and it will greatly increase the credibility of the candidate to be known by the voter.…”
Section: Introductionmentioning
confidence: 99%